Immunosuppression in paracoccidioidomycosis: T cell hyporesponsiveness to two Paracoccidioides brasiliensis glycoproteins that elicit strong humoral immune response - Benard, G.; Mendes-Giannini, Maria José Soares [UNESP]; Juvenale, M.; Miranda, E. T.; Duarte, A. J. S. (Univ Chicago Press, 1997)
To assess human cellular immune response to paracoccidioidomycosis (PCM), lymphocyte proliferative responses to purified antigens from Paracoccidioides brasiliensis were determined in healthy persons previously infected by the fungus (positive donors), in healthy noninfected persons (controls), and in PCM patients. Affinity-purified gp70 and gp43, the two major antigens in humoral immune responses, were used, Both induced lymphocyte proliferation (gp43 species-specific) in positive donors but not in controls; healthy persons previously infected by Histoplasma capsulatum reacted to gp70 and not to gp43, A similar cross-reactivity in antibody response to gp70 was previously reported; however, antibody response to gp43 has been considered specific, Lymphocytes from PCM patients, who, unlike positive donors, have high levels of anti-gp43 and anti-gp70 antibodies, proliferated poorly with gp70 and gp43 but better with other stimuli, This dichotomy between humoral and cellular antigen-specific responses suggests a Th2 immune response in PCM, which may be related to failure to control the infection.